Reactions of Some Bidentate Ligands with Antimony Trichloride Adducts with Oxygen Donors-I - Rastogi, M.K. (Asian Journal of Chemistry, 2010)
Stable adducts of antimony trichloride with oxgen donor molecules(urea, formamide, acetamide, dimethyl formamide, benzamide, acetanilide,benzanilide, and DMSO) on treatment with bidentate ligands (8-hydroxyquinoline, dimethyl glyoxime, α-benzildioxime, γ-benzildioxime andsalicylaldoxime) in chloroform in 1 : 2 molar ratio (except γ-benzildioxime, 1 :1 ratio) produce stable complexes by replacing 2 chlorine atoms of theantimony trichloride molecule. Some physical characteristics of theproducts are reported and conclusions about their structural mode.